SIKAP PETANI PADI TERHADAP INOVASI MESIN RICE TRANSPLANTER DI KECAMATAN JUWIRING KABUPATEN KLATEN - Nur Rahmawati; Sapja Anantanyu; Arip Wijianto (Universitas Sebelas Maret, 2016)
This study aims to examine the attitude of rice farmers toward innovation of rice transplanter machine, the forming factors of farmers attitude, and the influence of factors that forms the attitudes with rice farmer's attitude towards rice transplanter machine. The location of study was determined intentionally in Subdistrict of Juwiring because the Subdistrict of Juwiring is one of the areas that received the highest rice transplanter machine compared to other subdistricts in Klaten Regency. The sampling method was Multistage cluster random sampling of 40 rice farmers. To determine the attitude and the forming factors of attitude used descriptive analysis. The Influence of the factors forming the attitude with the attitude of farmers toward rice transplanter machine was analyzed use multiple linear regression. The results showed that the attitude of the majority of farmers towards rice transplanter machine is doubtful. While the forming factors of attitudes, personal experience: the old farm classified as moderate; the influence of others classified moderate, formal education is classified moderate (secondary education), non-formal education clasified low, mass media classified very low, socialitistic classified moderate, wetland area classified moderate, and the nature of innovation classified moderate. There was a significant influence between personal experience, the influence of others, formal education, wetland area, nature of innovation and there was non-significant influence between non-formal education, mass media, socialistic with rice farmer's attitude towards rice transplanter machine.